Language Proficiency and Sonorant Devoicing in English Plosive-Sonorant Clusters - Klára Přečková; Pavel Šturm; Jan Volín (Research in Language)
This article explores the timing of phonetic voicing in plosive-sonorant clusters in English. VOT was measured in two groups of Czech learners with different proficiency levels and a native English control group. The hypothesis was that cross-language differences in the implementation of the voicing contrast would be reflected in lower devoicing by the non-native speakers, modulated by proficiency. 24 participants read a text with plosive-sonorant clusters (such as in plan or troops). The study found that less proficient speakers exhibited smaller degrees of devoicing compared to more proficient speakers, who however did not differ from the native controls. In line with the absence of devoicing in Czech secondary-school textbooks, the results provide insight into the interplay between language proficiency and pronunciation details in L2 acquisition.